Institutionalization of the Approval Principle of Majority Creditors for Bankruptcy Decisions in Bankruptcy Act Reform Efforts - Rian Saputra; Resti Dian Luthviati (Faculty of Law, Universitas Sebelas Maret, 2020)
This study aims to determine the urgency of institutionalizing the principle of bankruptcy decisions that must be approved by the majority creditors with a test stone in the form of a bankruptcy decision Number: 04/Pdt.Sus-PKPU/2018/PN.Niaga.Jkt.Pst then also to analyze the opportunities for institutionalizing the principle. mentioned in Indonesian law. This research is a normative legal research with an approach in the form of a conceptual approach, and a statute approach and a case approach. The results show that the urgency of applying the principle of